1987
DOI: 10.1161/01.cir.75.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Early atrial fibrillation during evolving myocardial infarction: a consequence of impaired left atrial perfusion.

Abstract: Seven of 214 patients (3%) with acute myocardial infarction (120 inferior and 94 anterior) developed atrial fibrillation within 3 hr of the onset of chest pain. All seven patients had an inferior infarction and in all seven the left circumflex artery was occluded proximal to the origin of its left atrial circumflex branch. In five patients this occlusion was acute and was the cause of inferior infarction and in the remaining two patients the occlusion was old and the inferior infarction was due to an acute occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 23 publications
1
59
1
1
Order By: Relevance
“…The higher incidence of AF during the first 24 hours could be explained by the fact that during the process of cell death there will be an increase in the release of catecholamine with electrolytes disturbances especially hypokalemia and hypomagnesaemia; this process ceases with the maturation of infarction. [19][20][21][22][23][24] Hod et al investigated the pathogenesis of AF in the early hours of an AMI in a population of patients who were admitted within three hours of the onset AMI. They suggested that acute left atrial ischemia is the patho-physiological mechanism of early AF.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of AF during the first 24 hours could be explained by the fact that during the process of cell death there will be an increase in the release of catecholamine with electrolytes disturbances especially hypokalemia and hypomagnesaemia; this process ceases with the maturation of infarction. [19][20][21][22][23][24] Hod et al investigated the pathogenesis of AF in the early hours of an AMI in a population of patients who were admitted within three hours of the onset AMI. They suggested that acute left atrial ischemia is the patho-physiological mechanism of early AF.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The causal etiologies of AF in the setting of AMI that have been fully established include atrial ischemia or infarction, pericardial inflammation, acute hypoxia or electrolytemetabolic imbalance, and hemodynamic impairment secondary to left ventricular dysfunction. [18][19][20][21] Additionally, endogenous or exogenous catecholamines may also contribute to AF. 22) Moreover, an association between AF and an increased incidence of severe ischemia and CHF and pump failure has also been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7A shows the number of AF events by group. The AF incidence rate ratio (IRR) was significantly higher in LCX compared with LAD (LCX versus LAD, IRR, 6 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; P=0.001) or control group (LCX versus control, IRR, 12 [3.26-44.14]; P<0.001, negative binomial model). In contrast, there was no significant differences in IRR between the LAD and control groups (IRR, 2 [0.47-8.5]; P=0.4).…”
Section: Conduction Velocitymentioning
confidence: 99%